Short term perinatal and obstetrics outcomes in singleton pregnancies with Oligohydramnios: a prospective study - Morudu, Lefihlile Ally (My University, 2021)
Background: Oligohydramnios is best defined as an amniotic fluid volume <5th centile expected for a certain gestational age. It is a common complication that affects from 0.8-5.5% of pregnancies and 12% of pregnancies that go beyond 41 weeks. Objectives: The objectives of this study were to describe the perinatal and obstetric outcomes as well as fetal and maternal co-morbidities in singleton pregnancies diagnosed with oligohydramnios, in a South African setting. Methods: This was a prospective longitudinal observational study conducted at the Chris Hani Baragwanath Academic Hospital’s fetal medicine and obstetric unit. Women were recruited over a period of six months following ultrasound diagnosis of oligohydramnios (amniotic fluid index <5th centile for gestational age). Sixty-one files were retrievable for analysis and descriptive statistical analysis was used. Results: The caesarean section rate for the study population was 59.0%, with 72.2% of caesarean sections performed for fetal distress. Among the 35 women with co-morbid conditions, 23 (65.7%) had hypertensive disorders of pregnancy. The low birth weight proportion was 62.3% and a majority of the neonates were born at <38 weeks of gestation (54.1%), with 16.3% of the fetuses having intrauterine growth restriction. Overall, 49.1% showed evidence of fetal distress, 20.4% had low Apgar scores and 8.2% had meconium-stained amniotic fluid. Thirteen live-born neonates (24.1%) required resuscitation and 35.2% were admitted to the neonatal intensive care unit. Conclusion: Oligohydramnios is associated with a high risk of caesarean section due to fetal distress. There is also an association with maternal hypertensive disorders. Patients with oligohydramnios should be managed with intensive antepartum and intrapartum surveillance to improve the perinatal outcomes
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Medicine in Obstetrics and Gynaecology, 2021